Cervicofacial necrotizing fasciitis and drugs - Egas, Laís Sara [UNESP]; de Carvalho Reis, Erik Neiva Ribeiro [UNESP]; da Silva, Leonardo Freitas [UNESP]; Bonardi, João Paulo [UNESP]; de Lima, Valthierre Nunes [UNESP]; Gomes Ferreira, Pedro Henrique Silva [UNESP]; de Deus, Ciro Borges Duailibe [UNESP]; Garcia, Idelmo Rangel [UNESP] (Wolters Kluwer, 2018)
Necrotizing fasciitis (NF) is a devastating disease that typically affects immunocompromised patients, chronically debilitated patients or drug users, but can also affect healthy patients. Necrotizing fasciitis can rapidly produce septic shock and requires immediate surgical management of the necrotic tissue. It is a bacterial infection that progresses rapidly and has a high mortality generally caused by aerobic and anaerobic bacteria. The patient was immunocompromised and drug user. During treatment, a combination of broad-spectrum antibiotic therapy with Ciprofloxacin and Metronidazole, besides the use of activated charcoal dressing composed of carbonized fabric and impregnated with 0.15% silver nitrate enveloped by layer of fabric without activated carbon, chemical–mechanical debridement with hydrogen peroxide, 0.9% saline, and povidone iodine. According to the patient presented, for the treatment of NF there is a need for broad-spectrum antibiotic therapy associated with surgical debridement, use of activated charcoal for antiseptic compression and general intensive care.
Keywords: Face; Infection; Necrotizing fasciitis